MULTIPLE INTELLIGENCES RESEARCH DALAM PENINGKATAN KUALITAS LEMBAGA PENDIDIKAN ISLAM - Wahidah, Evita Yuliatul (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2018)
AbstractThe essence of the theory of multiple intelligences according to Howard Gardner of nine types of intelligence is logic-mathematical, linguistic, visual-spatial, kinesthetic, musical, interpersonal, intrapersonal, and naturalist and existential. While Multiple Intelligence Research (MIR) is a research instrument that can provide a description of intelligence trends that greatly help efforts to improve the quality of educational institutions. In addition, MIR is an outstanding research that helps teachers discover student learning styles and by adhering to the principles of Multiple Intelligences and using teaching strategies in multiple intelligences that can help improve the quality of Islamic Education institutions. Departing from this paradigm, discussion of the implementation of MIR in terms of analyzing the tendency of the best learning styles to be an interesting discussion. Supported by important factors that influence the implementation of the Multiple Intelligence theory in learning activities provide an alternative for critics of analysis in the implementation of Islamic education. Keywords: Multiple Intelligence Research, The Quality of Institutions, Islamic Education